Selection and Evaluation of Candidate Reference Genes for Quantitative Real-Time PCR in Aboveground Tissues and Drought Conditions in Rhododendron Delavayi - Zhang, Lu; Cai, Yanfei; Zhang, Mingchao; Du, Guanghui; Wang, Jihua (Frontiers in Genetics, 2022)
There has been no systematic identification and screening of candidate reference genes for nor-malization of quantitative real-time PCR (qRT-PCR) results in Rhododendron delavayi to date. Therefore, the present study used GAPDH, Act, EF1, Tub-, Tub-5, UEC1, TATA, TATA-2, UEP, TIP41, and Ubiqutin to predict their stabilities on different above-ground tissues (matured leaves (ML), stem tips (STM), and flower buds (FB)) at different developmental stages (young and adult plants) using five statistical algorithms: Delta Ct method, BestKeeper, geNorm, Normfinder. The findings were confirmed using ML obtained from plants that had been stressed by drought. By using RefFinder with ML samples collected under drought conditions, it was determined that the first five most stable reference genes were GAPDH > UEC1 > Actin > Tubulin- > Tubulin—5, whereas the least stable reference gene was Ubiqutin. Additionally, under control conditions, UEC1, UEC2, Actin, and GAPDH were selected as the highest stable potential reference genes at the juvenile stage of R. delavayi with ML and STM. When ML and STM were combined with drought-stressed samples, TIP41, GAPDH, or their combination proved to be the most effective qRT-PCR primers. The findings will aid in the improvement of the precision and reliability of qRT-PCR data, as well as laying the groundwork for future gene functional studies in R. delavayi.